Determinants of Assets Under Management Growth in Indian Mutual Funds: Evidence from Ratings, Performance, and Fund Characteristics - Rahul Paul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
This paper investigates the determinants of Assets Under Management (AUM) growth in Indian mutual funds, with a focus on the role of information signals, past performance, and fund characteristics in a retail-dominated emerging market context. Drawing on signaling theory, the fund flow–performance literature, and behavioural finance, the analysis investigates how third-party ratings, historical returns, fund size, and expense ratios influence investor capital allocation decisions. Using cross-sectional data on mutual funds and multiple regression analysis with robustness checks, the findings show that fund ratings, past long-term performance, and fund size exert a positive and statistically significant effect on AUM growth, while expense ratios do not significantly influence investor flows. The results underscore the significance of information intermediaries and visibility effects in reducing information asymmetry in emerging capital markets, where retail investors heavily rely on simplified quality signals. By offering evidence from India on how behavioral biases and informational cues work together to influence mutual fund capital allocation, the study adds to the growing body of research on emerging market finance. This has consequences for investor protection laws, fund managers, and regulators.